2010
DOI: 10.1128/jcm.01778-09
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Scheme for Rapid Identification and Differentiation of Legionella pneumophila and Non- Legionella pneumophila Species

Abstract: A rapid two-step scheme based on PCR amplification and enzymatic digestion analysis of a 226-bp fragment of the 16S rRNA gene was developed to identify the Legionella genus by PCR amplification and to differentiate the Legionella pneumophila and non-Legionella pneumophila species by enzymatic digestion analysis. Among 42 ATCC strains (16 strains of L. pneumophila and 26 strains of non-L. pneumophila) and 200 Legionella isolates from environmental water samples, including pools, rivers, lakes, and cooling tower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this study, a nested PCR was utilized to define Legionella positive water samples. The two paired primers showed high specialty for Legionella which had been described by Cloud JL et al (Cloud et al, 2000) and our research group (Zhan et al, 2010). From these seventy-six water samples, forty-two were Legionella positive according to the PCR results.…”
Section: Polymerase Chain Reaction (Pcr) Test For Water Samplesmentioning
confidence: 84%
“…In this study, a nested PCR was utilized to define Legionella positive water samples. The two paired primers showed high specialty for Legionella which had been described by Cloud JL et al (Cloud et al, 2000) and our research group (Zhan et al, 2010). From these seventy-six water samples, forty-two were Legionella positive according to the PCR results.…”
Section: Polymerase Chain Reaction (Pcr) Test For Water Samplesmentioning
confidence: 84%
“…PCR analysis and restriction enzyme analysis (REA) : PCR detection of the 16S rRNA gene and REA were used for identification and confirmation of L. pneumophila standard strains and environmental isolates 9 . The restriction enzyme Taa I (HpyCH4III endonuclease, Thermo-Scientific Ltd., USA) was used for the differentiation of L. pneumophila and non- pneumophila Legionella species.…”
Section: Methodsmentioning
confidence: 99%
“…We also utilized a two-step assay derived method which we have previously report as a rapid and accurate means to detect and differentiate L. pneumophila and non-L. pneumophila to detect the Legionella from patient's sputum specimen. Zhan et al (2010) has reported that this two-step assay utilize 5 base sequence differences in the 16s rRNA gene between L. pneumophlia and non-L. pneumophlia to differentiate Legionella genus to different species (Zhan et al, 2010). This two-step assay include a genus specific PCR assay and a species specific enzymatic digestion analysis assay (Zhan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…PCR assay was previously described in our laboratory as a conventional method (Zhan et al, 2010). Genusspecific PCR primers amplified a 386-bp portion of the 16S rRNA gene (base 451 to base 837) of Legionella.…”
Section: Pcr-enzymatic Digestion Analysismentioning
confidence: 99%